Early Recovery of Salmonella from Food Using a 6-Hour Non-selective Pre-enrichment and Reformulation of Tetrathionate Broth - Daquigan, Ninalynn; Grim, Christopher J.; White, James R.; Hanes, Darcy E.; Jarvis, Karen G. (Frontiers in Microbiology, 2016)
Culture based methods are commonly employed to detect pathogens in food and environmental samples. These methods are time consuming and complex, requiring multiple nonselective and selective enrichment broths, and usually take at least one week to recover and identify pathogens. Improving pathogen detection in foods is a primary goal for regulatory agencies and industry. Salmonella detection in food relies on a series of culture steps in broth formulations optimized to resuscitate Salmonella and reduce the abundance of competitive bacteria. Examples of nonselective pre-enrichment broths used to isolate Salmonella from food include Lactose, Universal Pre-enrichment, Buffered Peptone Water and Trypticase Soy broths. Tetrathionate and Rappaport-Vassiliadis broths are employed after a 24-hour nonselective enrichment to select for Salmonella and hamper the growth of competitive bacteria. In this study, we tested a new formulation of Tetrathionate broth that lacks brilliant green dye and has lower levels of Tetrathionate. We employed this Tetrathionate broth formulation in conjunction with a 6-hour nonselective pre-enrichment period and determined that Salmonella recovery was possible one day earlier than standard food culture methods. We tested the shortened culture method in different nonselective enrichment broths, enumerated Salmonella in the non-selective enrichments, and used 16S rRNA gene sequencing to determine the proportional abundances of Salmonella in the Tetrathionate and Rappaport-Vassiliadis selective enrichments. Together these data revealed that a 6-hour nonselective pre-enrichment reduces the levels of competitive bacteria inoculated into the selective Tetrathionate and Rappaport-Vassiliadis selective broths, enabling the recovery of Salmonella one day earlier than standard culture enrichment methods.